BRANDING AS AN INSTRUMENT OF IMPROVING INVESTMENT ATTRACTIVENESS OF THE TERRITORY - M. Makashev (Вестник университета)
The article examines an ability of the territory brand to have an impact on consumers. It also discusses different ways to increase the investment attractiveness of the territory through the development of the brand's territory due to the possibility of additional revenues and reducing costs upon successful establishment and promotion of the territory brand, both from the territory itself, and on the part of investors.